Methodology and Engineering of a Sustainable Market Model - Lohosha, Roman; Krychkovskyi, Vadim; Moroz, Yevheniia; Kolesnyk, Tetiana; Vakar, Tetiana (European Journal of Sustainable Development, 2024)
The article presents the authors’ approach to the methodology (logic of cognition) of the market, the process of modelling a representative market with the proof of the possibility of appropriate management of the market state. The study was tested on the example of Ukraine’s vegetable market according to the development trends of the last 30 years. The functional model of the market was considered by the set of its functional factors and the possibility to identify market efficiency. It is substantiated that regulations should be considered through manipulation of a set of indicators and restrictions, which allows reducing market management to an essentially engineering task, the feasibility of which is determined by the dynamics of increase in the effects of market functioning. Keywords: market, market model, market functionality, market efficiency, market management